Indalecio Prieto enjuicia el papel del gobierno de la República en el estallido de la guerra civil - Marquina, Antonio (UNISCI Discussion Papers, 2006)
The document that we transcribe is a recording made by Indalecio Prieto at the home of Rafael and Guillermina Supervía, in Washington D.C. The recording is divided into tour parts. First, an introduction where Prieto tells how he was invited to Mexico and the desire of the exiled Republicans for returning to Spain. Then, an account of the 14 April events, with the establishment of the II Republic. The third part deals with the military coup on 17 July, which is related to the last part of the document, on Prieto’s opinion about Manuel Azaña.